Changes in Modern Pollen Assemblages and Soil Geochemistry along Coastal Environmental Gradients in the Everglades of South Florida - Yao, Qiang; Liu, Kam-biu (Frontiers in Ecology and Evolution, 2018)
This study aims to document the changes in modern pollen assemblages and soil elemental chemistry along broad edaphic, hydrological, and salinity gradients, including a previously undocumented secondary environmental gradient, in a vast mangrove-dominated wetland region in the Everglades, south Florida. Twenty-five soil surface samples were collected along an interior wetland transect and an estuarine mangrove transect across coastal zones in the Everglades National Park and subjected to palynological and XRF analyses. Modern pollen spectra from the sampling sites were classified into five a priori groups—wet prairie, pineland, inland mangroves, coastal mangroves, and fringe mangroves, based on the five vegetation types and sub-environments from which they were collected. Discriminant analysis shows that all (100%) of the samples are correctly classified into their a priori groups. On a broad scale, the modern pollen assemblages in surface samples collected from different vegetation types reflect the primary environmental gradient in the Florida Coastal Everglades. A distinct salinity and chemical gradient is also recorded in the XRF results, and the complexity of these gradients is captured at both regional and local scales. At the regional scale, concentrations of all the elements increase from terrestrial toward coastal sites. At the local scale, XRF results show a progressive decrease in most chemical concentrations and in the Cl/Br and Ca/Ti ratios away from the Shark River Slough at each individual site, suggesting that a secondary fluvial/tidal gradient also exists locally as a function of the distance from the river, the main carrier of these chemicals. This study provides new evidence to show that tidal flooding from the Shark River Estuary is directly related to the nutrient availability in the surrounding mangrove forests. These data will deepen our understanding of the environmental drivers behind the vegetation zonation in the region, especially in the mangrove ecosystems, and fill a gap in the pollen data network for the Everglades.